Water‐Stable Coordination Polymers as Dual Fluorescent Sensors for Highly Oxidizing Anions Cr2O72− and MnO4 - Zhang, Xiu‐Du; Zhao, Yue; Chen, Kai; Jiang, Yu‐Fei; Sun, Wei‐Yin (Chemistry, an Asian journal, 2019)
Due to their striking optical properties, luminescent coordination polymers as sensors for the detection of hazardous species have drawn interest of researchers in consideration of the control of environmental pollution. In this work, the organic ligand 2‐(4‐((E)‐2‐(pyridine‐2‐yl)vinyl)styryl)pyridine (2‐bpeb), which possesses a large π‐conjugated system, was employed to react with d10 metal ions to obtain novel luminescent coordination polymers. Three complexes [Cd(2‐bpeb)0.5(CNA)(H2O)] (CP1), [Cd(2‐bpeb)0.5(NDC)] (CP2) and [Zn(2‐bpeb)(BDC)] (CP3) were synthesized successfully by introducing carboxylic acids of 4‐carboxycinnamic acid (H2CNA), 2,6‐naphthalene dicarboxylic acid (H2NDC) and 1,4‐benzenedicarboxylic acid (H2BDC) as auxiliary ligands. Because of the existence of the large π‐conjugated system and d10 metal ions, all of these coordination polymers exhibit striking fluorescence properties. Impressively, all of them can function as sensors for the detection of highly oxidizing anions MnO4− and Cr2O72−, with an increased sensitivity for MnO4−. Three′s a crowd: Three novel coordination polymers based on a π‐conjugated ligand, 2‐(4‐((E)‐2‐(pyridine‐2‐yl)vinyl)styryl)pyridine (2‐bpeb), can function as chemical sensors for Cr2O72− and MnO4− in aqueous media.